2013
DOI: 10.1111/bjd.12289
|View full text |Cite
|
Sign up to set email alerts
|

Loss-of-function mutation inAAGABin Chinese families with punctuate palmoplantar keratoderma

Abstract: A novel loss-of-function mutation within AAGAB associated with PPPK was identified from two Chinese pedigrees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…The causative mutation, c.451 + 1G>A, was shown to result in exon 4 skipping, which is predicted to cause an in‐frame deletion of 30 amino acids in p34, eliminating part of the p34 Rab‐like GTPase domain, which may play a role in vesicle trafficking . These data are in line with three recent reports, which have shown that PPKP1 results from haploinsufficiency for AAGAB . However, in contrast to these previous reports, the mutation reported in the present study was found to be associated with a complex phenotype including PPKP and CDH.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The causative mutation, c.451 + 1G>A, was shown to result in exon 4 skipping, which is predicted to cause an in‐frame deletion of 30 amino acids in p34, eliminating part of the p34 Rab‐like GTPase domain, which may play a role in vesicle trafficking . These data are in line with three recent reports, which have shown that PPKP1 results from haploinsufficiency for AAGAB . However, in contrast to these previous reports, the mutation reported in the present study was found to be associated with a complex phenotype including PPKP and CDH.…”
Section: Discussionsupporting
confidence: 83%
“…PPKP1 has recently been shown to be associated with mutations in the AAGAB gene , and in a single case, in the COL14A1 gene . AAGAB encodes the α‐ and γ‐adaptin binding protein p34, which plays a role in clathrin‐coated vesicle trafficking .…”
Section: Introductionmentioning
confidence: 99%
“…To date, 12 AAGAB mutations have been reported in European, African and Asian populations (9)(10)(11). Four mutations are in the Rab-like GTPase domain, 3 mutations are within the adaptin-binding domain and 4 mutations lie upstream of the Rab-like GTPase domain.…”
Section: Discussionmentioning
confidence: 99%
“…PPPK can be associated with malignancies, such as lung cancer, Hodgkin's disease, breast cancer and prostatic carcinoma (3) 7refined localisation of a PPPK gene to a region at 15q22.2-15q22.31 and a locus to only 0.967 Mb at chromosome 15, respectively. Recently, pathogenic mutations of AAGAB and COL14A1 genes in PPPK pedigrees have been reported (8)(9)(10)(11).…”
mentioning
confidence: 99%
“…AAGAB encodes the alpha and gamma adaptin binding protein p34, and is located on chromosome 15q.22, within our previously identified linkage region ( Martinez-Mir et al , 2003 ). Since this finding, four subsequent studies have described mutations in AAGAB that underlie punctate PPK in several new families ( Cui et al , 2013 ; Kiritsi et al , 2013 ; Li et al , 2013 ; Pohler et al , 2013 ), revealing nine new and two recurrent mutations. In light of these recent findings, we sequenced the whole AAGAB gene in our cohort of 11 families presenting with punctate PPK lesions ( Supplementary Figures 1–11 ).…”
Section: To the Editormentioning
confidence: 91%